Effectiveness of Aloe Vera and Betel Leaf (Piper Betle L.) Spray on the Healing of Perineal Wounds - Saidah, Halimatus; Putri Wahyu Wigati; Dhita Kris Prasetyanti; Sutrisni; Galuh Pradian Yanuaringsih (Universitas STRADA Indonesia, 2025)
Perineal tissue wounds occur either spontaneously or through episiotomy after childbirth. The combination of aloe vera and betel leaf can be used as an alternative therapy. The purpose of this study was to determine the effectiveness of Lisih spray, a mixture of aloe vera and betel leaf perineal wound healing. The study design used a quasi-experimental study, with a population of 32 postpartum women on day 1 (second-degree perineal wounds). The study instrument used a REEDA Score.